The Rise of Scalable Micro/Nanopatterning - Ke Du; Ishan Wathuthanthri; Chang-Hwan Choi (Micromachines, 2017)
This is the golden age of scalable micro/nanopatterning, as these methods emerge as an answer to produce industrial-scale nano-objects with a focus on economical sustainability and reliability.[...]